A study of seed vigour test methodology variables : a thesis presented in partial fulfilment of the requirements for the degree of Master of Applied Science in Seed Technology at Massey University - Zhang, Tao (Massey University, 1998)
Further research of some variables and procedures for promising seed vigour tests, such as the conductivity, Accelerated Ageing (AA) and Controlled Deterioration (CD) tests, is needed for their wider application and standardisation. Experiments to determine the effects of fungicide and insecticide seed treatments, and breaking hard seed using concentrated sulphuric acid (H2SO4) and mechanical scarification on results of the conductivity and AA tests; determining tolerances for the conductivity test; and a comparison of the efficiency of two methods of raising seed moisture content (SMC), i.e., the water added method (WAM) and the filter paper method (FPM) for the CD test; were carried out using a number of seed species and methodology according to the procedures recommended by the International Seed Testing Association (ISTA) and its Vigour Test Committee. At the recommended application rate, protectant and systemic fungicide seed treatments had little effect on seed conductivity of the large seeded legumes garden pea (Pisum sativum L.), soybean (Glycine max. (L.) Merril), French bean (Phaseolus vulgaris L.) and broad bean (Vicia faba L.), and the cereals maize, sweet corn (Zea mays L.) and wheat (Triticum aestivum L.) both immediately after treatment and after two months storage. However, at double the application rate, systemic fungicide seed treatments significantly increased conductivity, but not necessarily for all the species, cultivars and chemicals used. Seed treated at the recommended fungicide application rate can be directly tested for conductivity without removal of the chemicals. Seed treatment chemicals, particularly insecticides, tended to increase conductivity of the small seeded legume white clover (Trifolium repens L.). However, the reliability of the conductivity test for small seeded legumes needs further investigation as the method currently recommended produced variable results. There was no clear trend for the effects of seed treatment chemicals on AA test results because different chemicals, particularly systemic ones, had different phytotoxicity, even at the recommended rate. However, when comparing the vigour of seed lots treated with the same fungicide or insecticide at a similar application rate, the seed lots can be directly AA tested. The effects of the chemicals on seeds are modified by their phytotoxicity, and their beneficial effects that are determined by chemical application rate, physical condition of the seed lot, vigour status of the seed lot, fungal infection and storage time. The tolerances for differences between the highest and lowest conductivity result among four replicates of a seed lot for garden pea cv. Bolero were calculated as 4.77 and 5.56μS/cm/g at the 5 and 1% significance level respectively. The present tolerance of 5μS/cm/g recommended by the Vigour Test Committee of ISTA is appropriate for pea and other large seeded legumes. However it may be not suitable for cereals and small seeded legumes because of large differences in conductivity value among them. Both the WAM and the FPM provided a SMC for large seeded species of garden pea and maize very near the desired SMC for the CD test. Variability was small, and ranking of seed lot vigour did not differ between the two methods of raising SMC. The WAM provided a reasonably acceptable SMC in terms of mean and variance for the small seeded species onion (Allium cepa L.) and swede (Brassica napus var. napobrassica L.), but was very dependent on the accurate operation of the micropipette and improvement of SMC determination methodology after the CD test. Therefore the WAM, after further refinement, will be able to be used for the CD test, superseding the FPM. Artificial deterioration conditions i.e., high temperature of 40°C for 48h and 45°C for 24h at near 20% SMC induced high seed dormancy in swede seed lots of cultivars received from the United Kingdom and New Zealand, but the extent varied with cultivar and initial SMC. Pre-chilling and 20-30°C germination temperature broke the dormancy. Caution should be used when swede and its close species e.g., rape (Brassica napus L.) and other Brassica spp. are artificial ageing tested. H2SO4 treatment had little negative effect on germination of white clover and lotus (Lotus uliginosus Schk.), but significantly increased conductivity and reduced AA germination because of seed coat degradation and fungal invasion.
Keywords: Seed Testing Methodology; Seed Quality